The Formation of Indonesian VTuber Digital Identity: A Study of Expressive Speech Act - Siswanto, Anggreani Puspitasari; Kurniawati, Wira (Universitas PGRI Semarang, 2026)
This study investigates how expressive speech acts in Indonesian contribute to digital identity formation by an Indonesian Virtual YouTuber (VTuber). The research focuses on Mikazuki Arion, a VTuber on the YouTube platform, and aims to analyze how expressive speech acts such as praise, gratitude, greetings, complaints, and humor function in constructing a distinctive digital persona. Using a qualitative descriptive method with a sociopragmatic approach, data were obtained through observation and note-taking from Mikazuki Arion’s live broadcasts. The analysis examined the forms, functions, and pragmatic features of expressive speech acts that support self-representation in virtual communication. The findings show that expressive speech acts serve three key function in constructing VTuber identity: (1) establishing emotional intimacy and social bonds through repetition and affective language, (2) demonstrating authenticity and self-reflection via humor, irony, and stance softening, and (3) enhancing audience engagement through inclusive and performative interaction. These strategies enable Mikazuki Arion to present an appreciative, humorous, and relatable digital persona, reinforcing parasocial relationships and community belonging. The study concludes that expressive speech acts are not merely emotional expression but pragmatic tools for identity negotiation and relationship-building in digital interaction. Language thus becomes a central medium for performing self-representation and maintaining authenticity in Indonesian Vtuber culture, contributing to broader discussion of sociopragmatics and digital identity.